Exploring whole-genome duplicate gene retention with complex genetic interaction analysis - Kuzmin, Elena; VanderSluis, Benjamin; Ba, Alex N. Nguyen; Wang, Wen; Koch, Elizabeth N.; Usaj, Matej; Khmelinskii, Anton; Usaj, Mojca Mattiazzi; van Leeuwen, Jolanda; Kraus, Oren; Tresenrider, Amy; Pryszlak, Michael; et al. (Science, 2020)
Whole-genome duplication has played a central role in the genome evolution of many organisms, including the human genome. Most duplicated genes are eliminated, and factors that influence the retention of persisting duplicates remain poorly understood. We describe a systematic complex genetic interaction analysis with yeast paralogs derived from the whole-genome duplication event. Mapping of digenic interactions for a deletion mutant of each paralog, and of trigenic interactions for the double mutant, provides insight into their roles and a quantitative measure of their functional redundancy. Trigenic interaction analysis distinguishes two classes of paralogs: a more functionally divergent subset and another that retained more functional overlap. Gene feature analysis and modeling suggest that evolutionary trajectories of duplicated genes are dictated by combined functional and structural entanglement factors.